Evaluation of Anti-diabetic and Anti-hyperlipidemic Activity of Rhododendron arboreum bark extract against Streptozocin Induced Diabetes in Rats - Gautam, Suman; Chaudhary, Kabiraj (Journal of Medicinal Herbs and Ethnomedicine, 2020)
The anti-diabetic and anti-hyperlipidemic activity of R. arboreum in bark extract against streptozocin-induced diabetic rats. R. arboreum bark extract in ethanolic solution was prepared by soxhlatation method and stored in refrigerator for further use. The plant extract was tested for its hypoglycaemic property in glucose overloaded albino rats. The effect of extract was evaluated for its anti-diabetic action in STZ induced diabetic rats on 7, 14, 21 and 28 days respectively. Treatment with the ethanolic extract of Rhododendron arboreum significantly decreased blood glucose in diabetic rats and glucose overloaded rats, where as the extract also improved the others biochemical parameters associated with diabetes like total cholesterol, triglycerides and LDL were reduced and HDL level was increased .The cardioprotective and nephroprotective qualities of the extract was determined by measuring biomarker LDH in diabetic rats. The histopathology of pancreas was studied to support the experimental results. The histology of pancreatic islet cells was normal in non-diabetic animals, whereas in diabetic treated rats. The significant percentage reduction of glucose level was found to be 44.78% at the dose of 200 mg/kg of aqueous extract of Rhododendron arboreum at 28th day of the treatment.